Effect of aggregate petrology on the durability of asphalt pavements. (15th August 2017) - Anastasio, Sara; Perez Fortes, Ana Patricia; Hoff, Inge
Highlights: The petrographic analysis of rocks is not considered for their application. Asphalt performance depends on the rock quality. Hydrophilic minerals and micro-cracks are important information. Abstract: A petrographic analysis of the aggregates, generally carried out in the quarry exploration phase, gives information about fundamental characteristics on which all the others, including mechanical resistance, depend. However, in the asphalt industry the interest is often limited to the mica and sometimes quartz content. This article aims to expose the limitation of the current asphalt concrete design method compared to the advantages given by a deeper analysis of the stone material properties through an analysis of the behavior of four asphalt mixtures subjected to durability tests. The findings support the importance of the evaluation of the geological parameters.